Analysis Method of Gear Profile Deformation,Transmission Error and Contact Pattern - Wang Ruixin; Yang Chao; Gong Yu; Liu Hongqi; Zhang Jingcai; Li Jinfeng (Jixie chuandong)
By using the LTCA analysis of involute gear,gear tooth deformation and stiffness curve with load is obtained. Then a study of the effect on meshing stiffness of drum shape modification across of gear width and lead misalignment is carried out by using of slicing method. A convenient method of analyzing and calculating gear deformation curve is proposed,and to be used for obtaining the gear transmission error curve and contact pattern analysis for gear with profile modification and width modification. It is clear that this result is helpful for gear transmission error,the contact state analysis and modification optimization,this method is verified by Romax,an commercial software for gear transmission analyzing.